Cooperation between Public and Private Sector of Smart City Development - Thongmuenwai, Phuangpect; Kenaphoom, Assoc. Prof. Dr. Sanya (Journal for Developing the Social and Community, 2017)
Cooperation between public and private sectors of Smart City development in order to drive Khon Kaen become the Medical Hub of AEC, this concept has been developed in around the world by using digital technology or information and communication technology (ICT) for integrating on management the complex of city effectively to reduce management costs, reduce energy costs, increase convenient of people’ way of life, safety, good environment, better quality of life and development sustainably.